The rise of statistical thinking, 1820-1900 - Porter, Theodore M. (Princeton University Press, 2020)
"An essential work on the origins of statistics. The Rise of Statistical Thinking explores the history of statistics from the field's origins in the nineteenth century through to the factors that produced the burst of modern statistical innovation in the early twentieth century. Theodore Porter shows that statistics was not developed by mathematicians and then applied to the sciences and social sciences. Rather, the field came into being through the efforts of social scientists, who saw a need for statistical tools in their examination of society. Pioneering statistical physicists and biologists James Clerk Maxwell, Ludwig Boltzmann, and Francis Galton introduced statistical models to the sciences by pointing to analogies between their disciplines and the social sciences. A new preface by the author looks at the enduring relevance and significance of the book since its initial publication, and considers the current place of statistics in scientific research"--